Social Classes vs Professional Stereotypes in Greece. A View to a Fogy Social Construction - Kyridis, Argyris; Bassiou, Vasiliki; Zagkos, Christos; Golia, Paraskevi; Fotopoulos, Nikos; Papadakis, Nikos (Mediterranean Journal of Social Sciences, 2012)
In the context of the largest crisis that capitalism has ever faced the discussion on social class and class consciousnessseems more relevant than ever. The Greek crisis strikes as an ideal opportunity to start this debate. The phenomenal rise of the middleclass in Greece over the last four decades has shaped a very problematic framework for a deep and rational analysis of social classes incontemporary Greek society. The policy that had enabled public servants and small businessmen to have access to social goods - thatuntil a few years ago was exclusive privilege of the upper class – has changed the dominant model of interpretation of social stratificationand hierarchy in modern Greek society. This study by using a mixed questionnaire (Likert scale and Content Analysis of the written texts)investigates the class stereotypes and the class consciousness of the Greek youth, while trying to clarify the facts of class stratification inthe country in the midst of an unprecedented economic, social and political crisis.